THE FACTORS INFLUENCING RENAL RECOVERY IN CARDIAC SURGERY ASSOCIATED ACUTE KIDNEY INJURY - Zakon, K.; Romanova, V.; Tverdokhlib, K.; Dudarenko, V.; Arbuzova, I.; Radchenko, G. (Ukrainian Journal of Nephrology and Dialysis, 2016)
Background. In-hospital mortality of cardiac surgery patients with AKI is 3-7 times higher than those without AKI. This prospective observational study was dedicated to evaluate a differential approach of applying continuous and intermittent modalities in CS-AKIpatients on the rate and grade of renalfunction recovery. Methods. One hundred and six adult cardiac surgery patients admitted hospital in 2008-2011 years, who had AKI and met inclusion criteria were allocated in CRRTorIRRTgroup. Results. Sixty eight cardiac surgery with AKI patients who needed RRT were discharged from hospital. Among them, recovery of renalfunction was observed in 54 patients (79,4%) and 14 patients (20,6%) remained RRT-depen- dant. Complete recovery of renalfunction was reached in 33 patients (48,5%), while partial was observed in 21 patients (30,9%). Univariate analysis showed that complete recovery of renalfunction in CS-AKI significantly associated with reducing of dopamine dose during thefirst day of RRT (p=0,01) and long-term use of dobutamine (p=0,009). Partial recovery was associated with early dobutamine withdrawal (p=0,005) and absence of MOT (p=0,016), while RRT- dependence at discharge was associated with absence of MOT (p=0,006) and escalation of dopamine dose on thefirst day of RRT (p=0,025). The rate of renal recovery was statistically significantly higher in patients with CS-AKI with MOFthan inpatients with CS-AKI without MOF. In univariate analysis RRT-dependance at discharge of patients with CS-AKI with MOF was statistically significantly associated with arising of dopamine dose during thefirst day of RRT (p=0,006) and no-use of dobutamine at RRT start (p=0,006). Partial recovery was associated with early withdrawal of dobutamine (p=0,038). Discussion. Frequency of renal recovery inpresented study was higher than in VA/NIHAcute Renal Failure Trial Network study because of differences inpatients’population and corresponds to otherstudies of CS-AKIpatients. Conclusions. Recovery of renalfunction in CS-AKI patients associated with decreasing dose of dopamine, prolonged use ofdobutamine, illness severity and does not associated with specific RRT modality.